small and historic - Lidin, Konstantin (project baikal, 2021)
Small and historic towns reflect provinciality in every sense of the word. The collection of the materials presents today’s typical cases of small and provincial towns. In many towns, the search of local identity has just started, and its results are still rather questionable, because of the lack of an appropriate method. Should we search for a unique “face” of the town in its history and its sites with rich biography, like in blackearth Borisoglebsk? Or should we focus on the only unique object (Barabanovo on the Yenisei)? Or should we look back upon the town’s glorious past – its legendary fairs or unique production (Irbit in Ural)? These questions are also urgent for relatively big cities (but yet provincial).
Keywords: small and historic towns; provinciality; local identity